Rekondisi Rumah dan Inti Stator Bekas dan Rekonstruksi Koil untuk Keterbentukan Struktur Belitan Stator Alternator Fasetunggal - Marjuki, Marjuki; Hidayat , Alfian; Goeritno, Arief (JuTEkS (Jurnal Teknik Elektro dan Sains), 2023)
Work on the physical conditioning of the used stator housing and core and the reconstruction of a number of coils can be carried out for the establishment of a single-phase alternator stator winding structure. This work has been carried out in order to achieve two research objectives, namely (i) to recondition the physical condition of the used stator housing and core and (ii) to reconstruct a number of coils in the stator core. The research method for fulfilling the reconditioning stages includes cleaning the used stator housing and core, determining grooves, calculating and manufacturing for coil availability adjusted to the number of poles and coil winding type, installing the stator winding structure, and the calculation process in coil manufacture. Fulfillment of the stages of reconstruction of the coil at the stator core, including the installation of insulation, manufacture of a number of coils according to the determination of the number of poles, installation, connection and bonding of the coils, and calculation of the theoretical value of the output voltage and power.